Effect of rotator cuff muscle activation on glenohumeral kinematics: A cadaveric study. (22nd May 2020) - Williamson, Patrick M.; Hanna, Philip; Momenzadeh, Kaveh; Lechtig, Aron; Okajima, Stephen; Ramappa, Arun J.; DeAngelis, Joseph P.; Nazarian, Ara
Abstract: Healthy shoulder function requires the coordination of the rotator cuff muscles to maintain the humeral head's position in the glenoid. While glenohumeral stability has been studied in various settings, few studies have characterized the effect of dynamic rotator cuff muscle loading on glenohumeral translation during shoulder motion. We hypothesize that dynamic rotator cuff muscle activation decreases joint translation during continuous passive abduction of the humerus in a cadaveric model of scapular plane glenohumeral abduction. The effect of different rotator cuff muscle activity on glenohumeral translation was assessed using a validated shoulder testing system. The Dynamic Load profile is a novel approach, based on musculoskeletal modeling of human subject motion. Passive humeral elevation in the scapular plane was applied via the testing system arm, while the rotator cuff muscles were activated according to the specified force profiles using stepper motors and a proportional control feedback loop. Glenohumeral translation was defined according to the International Society of Biomechanics. The Dynamic load profile minimized superior translation of the humeral head relative to the conventional loading profiles. The total magnitude of translation was not significantly different (0.805) among the loading profiles suggesting that the compressive forces from the rotator cuff primarily alter the direction of humeral head translation, not the magnitude. Rotator cuff muscle loading is an important element of cadaveric shoulder studies that must be considered to accurately simulate glenohumeral motion. A rotator cuff muscle activity profile based on human subject muscle activity reduces superior glenohumeral translation when compared to previous RC loading profiles.